Meanings of the concept of national security. A historical review from the main ideologies of political modernity with emphasis on the role of public-private collaboration - Andriy Shtangret; Ruslan Skrynkovskyy; Lesia Stetsiv; Iryna Malyarchuk (Clío)
The concept of national security has evolved dialectically throughout history, under the influence of different political ideologies. In general, its meaning has centered on territorial defense and protection of the state, but its scope is now broadening to include aspects such as economic, food and cyber security. In essence, all contemporary notions of national security agree that this phenomenon is the result of public-private collaboration that also promotes a culture of civil society participation, recognizing that security is a shared responsibility between the State and citizens. From the perspective of the history of political ideas, for which concepts are not metaphysical entities, but a particular reflection of the time and space where they are produced, to explain certain phenomena and justify the interest of power actors, the objective of this research is to describe the meanings acquired by the concept of national security in different political and ideological discourses of Western modernity. It is concluded that, from liberal narratives that promote international cooperation to nationalist positions that prioritize the sovereignty of the nation-state, each discourse offers a different view of what it means to protect a nation.